Analysis of School Strategy in Efforts to Improve Sustainable Quality at MTs Miftahul Jannah, Langkat Regency - Nasution, Lukman; Rizkina, Seila (Jurnal Riset Ilmu Pendidikan, 2025)
This research aims to analyze the strategy of MTs Miftahul Jannah Langkat Regency in improving quality sustainable. This research uses a qualitative method with a descriptive analysis approach. The primary data source in this research is the principal’s school, while the secondary data sources are the deputy principal for Curriculum, teacher representatives and the school committee. The data collection techniques used in this research are: (a) observation, and (b) interviews. Data validity tests in qualitative research include: (a) credibility testing, (b) transferability testing, and (c) dependability testing. Data management and analysis techniques in this research go through the process of: (a) classification or description, (b) reduction or researcher focus, and (c) selection or interpretation. Based on the research results, it can be concluded that the school's strategy for sustainable quality improvement consists of: (1) the factual conditions of MTs Miftahul Jannah Langkat Regency consisting of: school program planning, implementation of school programs, and monitoring and evaluation of school programs. (2) the school's strategy for improving the quality of education through the Total Quality Management approach at MTs Miftahul Jannah Langkat Regency, and (3) supporting and inhibiting factors for implementing TQM.